PENGARUH IKLAN KOSMETIK WARDAH HALAL DARI AWAL DI TELEVISI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN WARDAH DI PEKANBARU - Ella Lestari; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Cosmetics industry and abroad pace in marketing the product in order to determine the success of corporate goals. Marketing communication is an effort to deliver the message to the public, especially the target target of the existence of products in the market. Advertising (advertising) is one of the most commonly used ways companies use to target audiences. This media is considered most effective in influencing consumers to make purchases. Advertising often leads the audience to believe in the product, thus encouraging potential customers to consume and maintain consumer loyalty. Wardah is the first cosmetic to have a halal TV commercial on television. Wardah cosmetic advertisement halal version from the beginning is the first cosmetic advertisement with halal theme. The purpose of this research is to know how big influence of kosher Wardah cosmetic advertisement from beginning in television to consumer purchasing decision in Pekanbaru.This research is done by explanative quantitative research method and technique done in collecting data that is questioner, and also use documentation. Population of this research is consumer wardah in Pekanbaru counted 96 responden.Teknik sampling from this research is accidental sampling. To know how big influence between variable X and variable Y, researcher use simple linear regression analysis. While to process the test data questionnaire, done with the help of Statistic Program and Service Solution (SPSS) program Windows version 22.0. The theory in this study using Stimulus - Response with the help of Dagmar model. These purchasing decisions are influenced by ad stars, ad themes, advertising slogans, advertising messages and ad illustrations. In the beginning prospective consumers wardah from not know to know, then understand and bear fruit beliefs that affect the purchase decision to buy wardah products.Result of research indicate that there is influence of kosher wardah cosmetic advertisement from beginning to consumer purchasing decision wardah in pekanbaru. With the value of simple analysis result (r) is 0.1901 da r2 (rsqaure) of 0.34 or 34% and it can be concluded that kosher Wardah cosmetic advertisement from the beginning on television to consumer purchasing decision in Pekanbaru able to influence purchase decision significantly. The effect of 55.8% belongs to the category of influence is quite strong.